ANALISA LAPORAN ARUS KAS SEBAGAI ALAT BANTU DALAM PENILAIAN KINERJA KEUANGAN PADA PDAM TIRTA MANAKARRA - Rostiaty Yunus (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2015)
This study aims to determine whether the Regional Water Company Tirta Manakarra already using the Statement of Cash Flows in assessing financial performance. As for the method of analysis used in this research is quantitative descriptive analysis method with a comparative analysis techniques as well as horizontal and vertical analysis of financial ratios. From the discussion and analysis showed Horizontal analysis of the cash flows in 2010-2012 continues to increase each period. Analysis vertically to increase and decrease the flow of cash and cash equivalents, for the comparison of operating activities and investments have increased, while the funding activities decreased quite dramatically. Based on the evaluation of financial performance through results pebandinganCash Flow Return On Debt And Equitypada in 2010 at 0.05 and increased in 2011 as much as 0.12, and so also in the year 2012 as many as 0.12.